Exoticism in Photography: Jean Mohr, Bandung-Jakarta, December 1973 - Ajidarma, Seno Gumira (Fakultas Film dan Televisi - Institut Kesenian Jakarta, 2024)
Historically, the age of colonisation constructs the cultural map of the world, which, after decolonisation, gives way to exotic views, which, through postcolonial criticism, arrive in Segalen’s thought, called symbolist exoticism. This concept is useful for discussing Jean Mohr’s photographs taken from inside a Pullman carriage on his journey from Bandung to Jakarta in December 1973. This article is a preliminary attempt to uncover the cultural construct behind the exotic moments of specific-movements captured by Jean Mohr’s camera.